The “Problem” of Male Friendship in Supernatural and Its Fan Fiction - Melodie Cardin ([sic])
This article considers the inclusion of the real-life “slash” fandom in the canon storyline of the CW/WB show Supernatural, and the consequent exploration of the taboo idea raised by the fans: of a sexual relationship between its two central characters, who are brothers. By including references to fan fiction, Supernatural opens a space to question normative sexual identity constructs. This article draws on an argument by Michel Foucault that homosexuality is a social construct that emerged as a way to deal with the “problem of male friendship.” In the context of Foucault’s argument, Supernatural’s treatment of its “slash” fan fiction allows for polysemic interpretations of the brothers’ relationship to coexist with the platonic “canon” storyline, opening the door to ideas of sexual fluidity and the “queering” of its characters by fans.Keywords: fan fiction, sexual identity, Foucault, intimatopias, Supernatural Supernatural is an American primetime show centered on a monster-of-the-week mystery format, led by the fictional brothers Sam and Dean Winchester (played by Jared Padalecki and Jensen Ackles), hunters of supernatural phenomena. In the fourth season, the brothers are in the midst of their usual investigation when they discover a book series that tells their own life story. As they begin to investigate this odd phenomenon, they discover that this book series has fans. Thus, the show’s real-life fandom is integrated into the “canon” storyline. What follows is an immediate reference to “slash” (“The Monster”).